Etika Dalam Konteks Keagenan Organisasi Nirlaba - Alamsyah, Ahmad Fahrudin (ULUL ALBAB Jurnal Studi Islam, 2002)
This study tries to dig ethics problems related to an agent relationship among principal (donor) and agent (management). Agent relationship structure can be drawn in equity theory construction, being based on SFAS No. 117 by three characteristic restricted net asset (unrestricted, temporary restricted, and permanently restricted). Ethics problems anticipated will be relevant to its storey; level restricted net asset, and the solution which on the market public monitoring through financial reporting and audit Â·which the standard. Last, the non profit organizational complexity requires assessment of agent efficiency done not only quantitatively but also qualitatively so that the ethics approach suitable to implement at this organizational type.